Desarrollo de un sistema de gestión ambiental de residuos sólidos urbanos del cantón Quero, provincia de Tungurahua. - Cajo Solano, Sonia Alexandra (2023)
Currently, the Municipal Decentralized Autonomous Governments (GADM) have the goal of improving the quality of life of citizens, where the management of solid waste generated stands out, since poor management of this can cause environmental pollution problems and seriously affect the health of the residents, therefore the main objective of the research is to develop a management system for urban solid waste in the Quero Canton, to strengthen environmental sustainability processes. For which a qualitative and quantitative approach was used, under a descriptive study, the information was collected through a bibliographic search and the application of surveys to a sample of 105 residents of the canton, in addition the Technical Design methodology was used for the management of MSW, which allowed the waste to be characterized by identifying its density, volume, type, etc. As results, it was determined that the current waste management is inefficient for the population since it does not cover all the waste generated, the average density of the waste was 140.8 kg/m, the type of waste was mostly organic, plastic and cartons. In addition, a proposal was prepared for a new sanitary landfill, the same one that will be located in the community of Huancalga Chico, of a semi-mechanized type with a useful life of 15 years.